The influence of microwave electromagnetic radiation on rat heart morphogenesis during thyroidectomy - O. O. Drobakhin; V. I. Magro; V. V. Kosharnyi; V. H. Rutgaizer; L. V. Abdul-Ohly (Regulatory Mechanisms in Biosystems, 2021)
It is known that electromagnetic radiation affects the functional systems of living beings, in particular, the endocrine and cardiovascular systems and directly the heart cells and their functioning. In this case, the influence of electromagnetic radiation significantly affects the properties of the cardiovascular system and changes physiological processes in it. Moreover, sensitivity to signals is higher for biosystems with a higher level of organization. The method of simulating hypothyroidism for rats makes it possible to develop an experimental model for analyzing morphogenetic changes in the rat heart. Under conditions of hypothyroidism modeling, destructive changes in muscle fibers are observed in the myocardium after thyroidectomy, but after microwave irradiation with an exposure of 45 minutes, a regenerative-compensatory reconstruction of the structural components of the myocardium of the heart wall occurs. After thyroidectomy and microwave irradiation with an exposure of 120 minutes, an increase in degenerative and destructive processes in the heart myocardium was observed. For the first time, a comparative ultramicroscopic study using electron microscopy was carried out. It showed that after electromagnetic irradiation with an exposure of 45 minutes, the general structure of the mitochondrial apparatus does not change. Irradiation with an exposure of 120 minutes causes the destruction of subsarcolemal and paranuclear organelles, edema and degradation of intermyofibrillar mitochondria. After exposure to electromagnetic radiation with the exposure of 45 minutes in a hypothyroid state, a compensatory restructuring of the energy apparatus of the contractile cardiomyocytes of the left ventricle occurs due to the formation of mitochondria and an increase in their contact interaction. After exposure to radiation for 120 minutes, the development of destructive-degenerative processes in the mitochondrial apparatus of left ventricular cardiomyocytes, deepening of damage to intermitochondrial contacts was observed. The most significant increase in the relative volume of the endothelium in the areas of the rat heart myocardium was observed for the case of microwave irradiation only (without experimental hypothyroidism) with exposure duration of 45 minutes. Immunohistochemical study both for the case of microwave irradiation only and for the case of microwave irradiation under conditions of experimental hypothyroidism allows us to conclude that morphogenetic transformations are highly active in the myocardium of the heart when the duration of exposure is 45 minutes. This study will make it possible to develop recommendations for persons with thyroid diseases on the duration of daily exposure of staying in electromagnetic field emitted by devices with characteristics similar to the case under study.